ACK Skipping: enabling QoS for multimedia communications in WiFi hot spots. (10th July 2006) - Vollero, Luca; Iannello, Giulio
In recent years the idea of access network has changed radically, and the diffusion of wireless technologies, and especially IEEE 802.11 compliant devices, has made wireless connections increasing popular. Despite the great success of the IEEE 802.11 standard, several problems concerning security, power consumption and quality of service of wireless LANs remain partially unsolved. The QoS issue is especially relevant for multimedia communications, generally needing performance guarantees from the network infrastructure to fulfil application requirements. In this paper we analyse through simulations, the ACK Skipping (ACKS) mechanism, a QoS mechanism for multimedia communications, and we compare it with EDCA, the Access Mechanism provided by the upcoming IEEE 802.11e standard. Simulation results show that, although EDCA achieve better overall channel utilisation, ACKS behaviour is comparable with that of EDCA under all the main performance indices, and it exhibits effective traffic differentiation capabilities.